Evidence of English language proficiency and academic achievement of non-English-speaking background students - Oliver, Rhonda; Vanderford, S.; Grote, E. (Routledge, 2012)
The increasing number of international students enrolled in Australian universities over the last decade has met with a corresponding concern that many non-English-speaking background (NESB) students experience considerable difficulty in their courses. Consequently, concerns about admission procedures have been raised regarding how English language proficiency (ELP) is determined for NESB students (both domestic and international). In addition to standardised ELP tests, some universities accept other forms of evidence, such as the completion of English-medium courses. This large-scale quantitative study analysed data on 5675 undergraduate and postgraduate students available from one university's database over a three-year period to ascertain if its ELP requirements were sufficient to ensure the academic progress of adequate numbers of these students. The best evidence for potential academic success was found to be standardised tests while students submitting other forms of ELP evidence tended to have more difficulties.